Vous êtes sur la page 1sur 1

u n u dx = u n du = u n+1 + C

n+1

1

u

u dx =

u 1 du = ln |u| + C

a u u dx = a u du =

u

a + C

a

ln

(n

= 1)

(a > 0, a

= 1)

sin u u dx = sin u du = cos u + C

cos u u dx = cos u du = sin u + C

1

2 u u

cos

dx =

1

2 u du = tan u + C

cos

1

2 u u dx =

sin

1

2 u du = cot u + C

sin

u dx u 2 +a

2 =

du u 2 +a 2 =

1

a arctan u +

a

1

C 1 = a arccot u + C 2

a

u dx u 2 a

2 =

du u 2 a 2 =

2a ln

1

ua

u+a

+ C

u 2 ±a 2 = u 2 ±a 2 =

u dx

du

ln u + u 2 ± a 2 + C

u dx

u 2 =

a 2

du

u 2 = arcsin u + C 1 = arccos u + C 2

a

a

a 2